Marketing Post-Feminism Through Social Media: Fan Identification and Fashion on Pretty Little Liars - (:unkn) unknown (My University, 2014)
Television shows targeted to a young, female audience often depict post-feminist themes such as self-sexualization, self-branding, consumerism, female empowerment through the body, and the "good" girl. This thesis focuses on the ABC Family hit series Pretty Little Liars as an example of the ways in which television shows promote these post-feminist ideologies. I argue that as the network has branded itself as the place for millennial programming; it has used digital platforms to make Pretty Little Liars a one-stop-shop for young women to learn about beauty and femininity. Relatedly, this project analyzes the ways in which young women construct their identities and online self-brands around the female characters on Pretty Little Liars and how, through the stars and costuming especially, the show inspires audiences both as a cultural phenomenon and an object of consumption.
Keywords: Fashion; Marketing; Post-Feminism; Pretty Little Liars; Self-Brand; Social Media